Konflik Agraria: Sebuah Refleksi Hak Menguasai Negara Atas Tanah - Wiryani, Fifik; Najih, Mokhammad (Universitas Widya Gama Malang, 2023)
The state's right to control land as a principle is often problematic in practice. The problem generally lies with the state which tends to use land only for economic and oligarchic interests. As a result, the right to control the state whose function is to prosper the people cannot be realized. This research will reveal and analyze the background of the causes of the agrarian conflict in the village of Tegalrejo, Malang Regency, and provide an overview in a reflection of the state's right to control land. This research uses normative juridical research with statutory, historical and case study approaches which in this case are agrarian conflicts. The results of the research show that the state's right to control over land sometimes becomes a tool for state legitimacy to carry out land grabs. The right to control the state, which essentially serves as a legal framework to protect the public, has not been able to fully function ideally and properly. There is no significant difference between the New Order regime and the Reform Government regime in the management of state control rights, because both have a mode of appropriation by granting status of land rights and compensation. This is similar to what happened in the agararia conflict in Tegalrejo Village, Malang Regency, where legal appropriation was formulated in the form of Cultivation Rights. Compensation that has not been resolved to date has also led to the creation of structural agrarian conflicts that have disrupted the socio-economic life of the surrounding community. In the future, it is necessary to think about the rejuvenation of the concept of the state's right to control so that state control over land is no longer hegemonic and can be on a par with the protection of citizens' rights to land.